“A false sense of confidence” The perceived role of inflammatory point-of-care testing in managing urinary tract infections in Dutch nursing homes: a qualitative study - S. D. Kuil; C. Schneeberger; F. van Leth; M. D. de Jong; J. Harting (BMC Geriatrics, 2020)
Abstract Background Diagnosing urinary tract infections (UTI) in nursing home residents is complex, due to frequent non-specific symptomatology and asymptomatic bacteriuria. The objective of this study was to explore health care professionals’ perceptions of the proposed use of inflammatory marker Point-Of-Care Testing (POCT) in this respect. Methods We conducted a qualitative inquiry (2018–2019) alongside the multicenter PROGRESS study (NL6293), which assessed the sensitivity of C-reactive protein and procalcitonin POCT in UTI. We used semi-structured face-to-face interviews. The participants were physicians (n = 12) and nurses (n = 6) from 13 nursing homes in the Netherlands. Most respondents were not familiar with inflammatory marker POCT, while some used POCT for respiratory tract infections. Both the interview guide and the analysis of the interview transcripts were based on the Consolidated Framework for Implementation Research. Results All respondents acknowledged that sufficiently sensitive POCT could decrease diagnostic uncertainty to some extent in residents presenting with non-specific symptoms. They primarily thought that negative test results would rule out UTI and justify withholding antibiotic treatment. Secondly, they described how positive test results could rule in UTI and justify antimicrobial treatment. However, most respondents also expected new diagnostic uncertainties to arise. Firstly, in case of negative test results, they were not sure how to deal with residents’ persisting non-specific symptoms. Secondly, in case of positive test results, they feared overlooking infections other than UTI. These new uncertainties could lead to inappropriate antibiotics use. Therefore, POCT was thought to create a false sense of confidence. Conclusions Our study suggests that inflammatory marker POCT will only improve UTI management in nursing homes to some extent. To realize the expected added value, any implementation of POCT requires thorough guidance to ensure appropriate use. Developing UTI markers with high negative and positive predictive values may offer greater potential to improve UTI management in nursing homes.